2010
DOI: 10.1063/1.3525994
|View full text |Cite
|
Sign up to set email alerts
|

Micelles induced high coercivity in single domain cobalt-ferrite nanoparticles

Abstract: We have prepared CoFe2O4 nanoparticles in micellar medium by wet chemical technique and obtained very high coercivity value of 4.4 kOe at room temperature for particle size ∼16 nm. A large coercivity (∼20 kOe) is observed on cooling down to 2.5 K. We annealed the sample at different temperatures to check the role of micelles and particles size in the change in coercivity value. Here we observed micelles as capping agent playing an important role to enhance the coercivity, as after removal of micelles for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 17 publications
2
14
1
Order By: Relevance
“…Besides the mean diameter of the nanoparticles from sample CF4 being smaller than the critical size expected for the magnetic multi-domain regime [15], many big particles with a diameter larger than this critical size were observed in TEM images. Thus we conclude that particles in the multi-domain regime play an important role in magnetic behavior.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Besides the mean diameter of the nanoparticles from sample CF4 being smaller than the critical size expected for the magnetic multi-domain regime [15], many big particles with a diameter larger than this critical size were observed in TEM images. Thus we conclude that particles in the multi-domain regime play an important role in magnetic behavior.…”
Section: Resultsmentioning
confidence: 87%
“…In a recent article, Sato Turtelli et al [18] showed that samples prepared by mechanical milling present an i factor smaller than that obtained for samples synthesized by sol gel method. Another indicating that this sample is in magnetic multi-domain regime [15]. Thus the magnetization process is caused mainly by the movement of domain walls.…”
Section: If Co 2+ Ions Move From A-sites To B-sites and Consequently mentioning
confidence: 80%
“…The linear behavior follows the equation H C ( T )= H C (0)[1−( T / T B ) 1/2 ], in which H C ( T ) and H C (0) are the coercivity at temperature T and at 0 K, respectively. Our experimental calculated T B is 411.0182 K. The linear dependence of H C on T 1/2 is evidence of monodispersed, ferromagnetically ordered, single‐domain particles . It is an advantage to obtain such ferromagnetic properties at room temperature for the use of a material as a catalyst as it will help in the magnetic separation of the catalyst after its use without hampering the product present in the medium.…”
Section: Resultsmentioning
confidence: 99%
“…As temperature increases, maximum magnetization, coercivity, and remanence decrease (Figure 5d), as expected, due to the decrease in magnetocrystalline anisotropy. [48] Due to the temperature increase, nanoparticles internal energy increases, and the energy barrier that separates the energetically degenerated magnetic orientations decreases, thus a minor energy fluctuation lead to the switching of domains orientation. As a consequence of temperature increases, lower applied magnetic field is necessary to induce the maximum magnetization, lower amount of domains remains magnetized after magnetic field removal and consequently lower field is necessary to demagnetize the samples (Figure 5d).…”
Section: Magnetic Propertiesmentioning
confidence: 99%